Association between hearing loss and cauliflower ear in wrestlers, a case control study employing hearing tests - Noormohammadpour, P.; Rostami, M.; Nourian, R.; Mansournia, M. A.; Farahani, S. S.; Farahbakhsh, F.; Kordi, R. (Asian Journal of Sports Medicine, 2015)
Background: According to anecdotal findings, some wrestling coaches and wrestlers believe that cauliflower ear might lead to hearing loss. Our preliminary study showed that the prevalence of hearing loss reported by the wrestlers with cauliflower ear is significantly higher than this rate among wrestlers without cauliflower ear. To the best of our knowledge, no other study has confirmed this finding employing hearing tests.